2003
DOI: 10.1021/jp030757n
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Mechanical Studies of CH3ClO3 Isomers and the CH3O2+ClO Reaction Pathways

Abstract: The geometries, harmonic vibrational frequencies, and relative energetics of CH 3 ClO 3 isomers have been examined using quantum mechanical methods. At the G2MP2 level of theory, the lowest-energy structure is found to be the CH 3 OClO 2 form followed by the chain-type CH 3 OOOCl isomer located 7.9 kcal mol -1 higher. The QCISD(T) method predicts that the CH 3 OOOCl structure is located lower than CH 3 OClO 2 . The two higher-energy structures are CH 3 OOClO and CH 3 ClO 3 across all energy levels. Interisomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
38
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 26 publications
8
38
1
Order By: Relevance
“…TS8 is also located below reactants as already said, presenting no barrier for the isomerization CH 3 OOClO M CH 3 OClO 2 . Hence, the current calculations suggest that methyl chlorate may be formed as a reaction intermediate through either TS1 or TS8 and may participate in the mechanism of the reaction CH 3 O 2 + ClO, contrary to what has been originally assumed [10].…”
Section: Resultscontrasting
confidence: 88%
See 3 more Smart Citations
“…TS8 is also located below reactants as already said, presenting no barrier for the isomerization CH 3 OOClO M CH 3 OClO 2 . Hence, the current calculations suggest that methyl chlorate may be formed as a reaction intermediate through either TS1 or TS8 and may participate in the mechanism of the reaction CH 3 O 2 + ClO, contrary to what has been originally assumed [10].…”
Section: Resultscontrasting
confidence: 88%
“…An important new feature in the current work is the finding that methyl chlorate, CH 3 OClO 2 , although not a nascent association minimum, may also be formed as a reaction intermediate on the singlet surface directly from the reactants, opposite to what has been previously assumed [10]. Thus, CH 3 OClO 2 may be formed either from CH 3 O 2 + ClO through the newly determined transition state TS1 or through isomerization of the methoxy chlorite isomer, CH 3 OOClO, via transition state TS8.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…2,6,8 These systems are analogous to the reactions of HO 2 and CH 3 O 2 with the ClO and BrO radicals for which several experimental and theoretical studies have been reported. [9][10][11] It was found that the reaction of HO 2 +IO 12 displayed a rate coefficient, k= (8.4±0.3)×10 -11 cm 3 •molecule -1 •s -1 at 298 K and Drougas et al 6 suggested that the HO 2 and IO reaction proceed through the formation of the bound complexes, HOOOI and HOOIO. Two of the experimental studies have shown that the reactions RO 2 +IO are fast and may indeed have an important impact on ozone chemistry.…”
Section: Introductionmentioning
confidence: 99%